Exploring chinese accounting students’ acceptance of electronic learning using technological acceptance model - Liu, Rongrong (2021)
According to the COVID-19 epidemic prevention and control requirements, the Ministry of Education put forward the "no suspension of classes" initiative. Colleges and universities are opening e-learning programs. Through the online questionnaire survey, this study took 543 accounting students of Xi 'an University of Finance and Economics as the research objects. Through the online questionnaire survey, the research was carried out, and PLS-SEM software was used for data analysis. This paper discusses the factors that influence college students' actual use of e-learning from the perspective of perceived usefulness, perceived ease of use, attitude towards technology and behavioral intention. In this study, only behavioral intention and the actual use of e-learning had no significant impact. The other three objectives are the relationship between perceived usefulness, perceived ease of use and technology attitude, the relationship between perceived ease of use and technology attitude, and the relationship between technology attitude and behavior intention. Finally, it summarizes the theoretical and practical significance of the influencing factors of network learning. This study discusses the significance, limitations and approaches of future research.